(untitled) (Pedagogy of Higher and Secondary Education, 2022)
The basic tenets and status of humanitarian subjects and sciences have been illustrated. Practical approaches to appropriateness of professional foreign communication forming have been characterized. The aims and tasks pointing the position of humanitarian training in the system of technical university education have been formulated.